Irrigation Control System for Drip Irrigated Tomato in Greenhouse using Timer-based Control Method and Crop Water Requirement - Sanya Kuankid (Warasan Witthayasat Lae Theknoloyi Mahawitthayalai Mahasarakham, 2019)
This research on the drip irrigation management system for tomato cultivation in greenhouses aims to develop a small control system with precise control of the quantity and time of irrigation and fertilization. Controlling systems use small-board processors and timer-base modules to refer to an irrigation scheduling. The Penman-Monteith models were used to evaluate the water requirements in each tomato growth phase, using water flow sensors to measure and control the amount of irrigation in each time. The results showed that the percent error of accumulative amount of water by the control system was 7.01 percent without any control time error. The experiment measuring the growth period at 49 days found that the average stem height of plant was 153.17 cm. and the average diameter of the plant was 8.20 mm. In terms of yield and quality of tomato, the results found that the number of fruit, fruit weight per plant, fruit weight, fruit width, fruit length, and total soluble solid content were 396, 4,027 g, 10.85 g, 22.10 mm., 40.50 mm. and 9.82 degrees brix, respectively.